Efek Perbedaan Volume Tidal Intraoperatif terhadap Rasio Pao2/Fio2 Pascaoperasi Abdominal Mayor - Aditianingsih, Dita; Jefferson, Jefferson; Mandagi, Michael (Majalah Anestesia dan Critical Care, 2016)
Komplikasi paru pascaoperasi merupakan salah satu penyebab penting morbiditas dan mortalitas pascaoperasi yang berkaitan dengan anestesia dan pembedahan. Studi ini membandingkan volume tidal 6 mL/kgBB dan 10 mL/kgBB dengan menggunakan PEEP dan pengaruhnya terhadap komplikasi paru. Setelah mendapat persetujuan dari Komite Etik Penelitian Kesehatan FKUI/RSCM, dilakukan uji klinis acak terhadap 52 pasien operasi abdominal mayor elektif di Rumah Sakit Cipto Mangunkusumo pada bulan November 2014–April 2015. Subjek diacak dalam 2 kelompok, yaitu kelompok dengan volume tidal 6 mL/kg dengan PEEP 6 cmH2O dan volume tidal 10 mL/kg dengan PEEP 6 cmH2O. Keluaran primer adalah pemeriksaan fungsi paru menggunakan rasio PaO2/FiO2. Keluaran sekunder adalah komplikasi paru (pneumonia, atelektasis, ARDS, gagal napas), komplikasi ekstraparu (SIRS, sepsis, sepsis berat), dan mortalitas dalam 28 hari pascaoperatif. Tidak ditemukan perbedaan yang bermakna rasio PaO2/FiO2 antara kelompok VT-6 mL/kg dengan VT-10 mL/kg (p>0,05), baik pada awal operasi, akhir operasi, hari pertama pascaoperasi, dan hari kedua pascaoperasi. Tidak ada perbedaan bermakna pada semua keluaran sekunder diantara kedua kelompok. Simpulan, volume tidal 6 hingga 10 mL/kg dengan PEEP 6 cmH2O aman untuk dipakai pada pasien yang menjalani operasi abdominal mayor. Kata kunci: Operasi abdominal mayor, pemeriksaan fungsi paru, ventilasi mekanis, volume tidal The Effect of Intraoperative Tidal Volume Difference against Postoperative PaO2/FiO2 Ratio for Patients undergoing Major Abdominal SurgeryPostoperative pulmonary complications are closely related to postoperative morbidity and mortality associated with anesthesia and surgery. Mechanical ventilation setting affects postoperative pulmonary complications. This study aimed to compare the effect between tidal volume of 6 mL/kgBW and 10 mL/kgBW with PEEP and its effect on pulmonary complications. After approval from Ethics Committee Faculty of Medicine Universitas Indonesia, Cipto Mangunkusumo (RSCM) Hospital, a randomized clinical trial was done on 52 elective major abdominal surgery patients at RSCM Hospital from November 2014 to April 2015. Subjects were randomized into two groups: the group receiving tidal volume 6 mL/kgBW with PEEP 6 cmH2O (VT-6 group) and the group receiving tidal volume of 10 mL/kgBW with PEEP 6 cmH2O (VT-10 group). The primary output was the assessment of pulmonary function using the ratio of PaO2/FiO2. Secondary outputs were pulmonary complications (pneumonia, atelectasis, ARDS, respiratory failure), extrapulmonary complications (SIRS, sepsis, severe sepsis), and mortality within 28 days. Both groups showed similar baseline characteristics. There was no significant PaO2/FiO2 ratio differences between both groups (p>0,05) at the beginning of surgery, at the end of surgery, at the first postoperative day, and the second postoperative day. There was no significant difference in all secondary outcomes between both groups. The use of tidal volume of 6 to 10 mL/kg with PEEP 6 cmH2O was considered safe for patients undergoing major abdominal surgery. Key words: Major abdominal surgery, mechanical ventilation, pulmonary function tests, tidal volume